The Efficacy of Transversus Abdominis Plane Block for Analgesia in Comparison with Local Anesthetic Wound Infiltration Post-Cesarean Section: A Randomized Comparative Double-Blinded Clinical Trial - Mona Saad Salman; Ahmed Shaker; Heba Rady Elbassyouny; Ramy Mohamad Elnaggar; Mohamed Raslan; Ali Elsayed Khayal; Safaa Ibrahim Mahmoud (IMR Press, 2024)
Background: Cesarean section (CS) is one of the most common surgical procedures worldwide, often associated with postoperative pain. Effective pain management is crucial for maternal recovery and satisfaction. Transversus abdominis plane (TAP) block and local anesthetic wound infiltration (LWI) are commonly used techniques for post-cesarean analgesia. While both methods have shown efficacy, their comparative effectiveness remains debated. This study aims to compare the efficacy of TAP block versus LWI for post-cesarean analgesia, considering pain scores and opioid consumption, to provide insights into optimizing pain management strategies for women undergoing CS. Methods: A randomized comparative double-blinded clinical trial conducted on 200 randomly selected patients aged 20 to 40 years in the university hospital from January 2021 to January 2022 after receiving approval from the ethical research committee. Patients were divided into two groups. All patients were instructed on how to use the visual analog scale (VAS), and the procedure of ultrasound-guided TAP block or local anesthetic wound infiltration was explained to them. Main Outcome Measure: The level of pain during movement (hip flexion and coughing) at 2, 4, 6, 12, and 24 hours following surgery. Pain intensity was measured using a VAS score ranging from 0 to 10 (0 representing no pain, and 10 representing the worst conceivable discomfort). Results: Patients who underwent TAP block showed significantly lower pain scores for 12-16 hours after surgery and a reduced total requirement for analgesia in the first 24 hours after surgery compared to patients who received wound infiltration. Conclusions: Our study demonstrated that bilateral TAP block was more effective in reducing postoperative pain and total 24-hour postoperative opioid and analgesic consumption after cesarean section under spinal anesthesia compared to local anesthetic wound infiltration. Clinical Trial Registration: The trial was registered in ClinicalTrials.gov registry with clinical trial: https://clinicaltrials.gov/ct2/show/NCT05447455.